ECMO (extra corporeal membrane oxygenation) in major trauma: A 10 year single centre experience. Issue 9 (September 2021) - Amos, Timothy; Bannon-Murphy, Holly; Yeung, Meei; Gooi, Julian; Marasco, Silvana; Udy, Andrew; Fitzgerald, Mark
Highlights: ECMO use in major trauma patients was primarily for severe hypoxaemic respiratory failure. In this severely injured cohort overall survival was poor, but better in VV ECMO compared to VA. Survival was better if ECMO was initiated early (<72 hours) compared to late. Abstract: Aim To review the indications, complications and outcomes of extracorporeal membrane oxygenation (ECMO) in major trauma patients. Methods Single centre, retrospective, cohort study. Results Over a ten year period, from 13, 420 major trauma patients, 11 were identified from our institutional trauma registry as having received ECMO. These patients were predominantly younger (mean 39 +/- 17 years), male (91%) and severely traumatised (median ISS 50, IQR 34 - 54). Veno-venous (VV) ECMO was used predominantly (n = 7, 64%), to treat hypoxic respiratory failure (mean PaO2/FiO2 ratio 69.7 +/- 38.6), secondary to traumatic lung injury. Veno-arterial (VA) ECMO was used less frequently, primarily to treat massive pulmonary embolism following trauma. Major bleeding complications occurred in four patients, however only one patient died from haemorrhage. Heparin free (2/11), delayed (3/11) or low dose heparin (2/11) therapy was frequently utilised. The median time from injury to ECMO initiation was 1 day (IQR 0.5 – 5.5) and median ECMO duration 9 days (IQR 6.5 – 10.5). ECMO was initiated <72 hours in 6 patients, with survival to discharge 67%, compared to 20% in those initiated >72 hours. Overall survival to discharge was 45%, and was higher with VV ECMO (64%), than other configurations (25%). Conclusion ECMO was rarely used in major trauma, the most common indication being severe hypoxaemic respiratory failure secondary to lung injury. In this severely injured cohort, overall survival was poor but better in VV compared to VA and better if initiated early (<72 hours), compared to late.